Adaptive Initial Sizing Method and Safety Assessment for Hybrid-Electric Regional Aircraft - Nicolas Moebs; Dominik Eisenhut; Evert Windels; Jenny van der Pols; Andreas Strohmayer (Aerospace, 2022)
In the wake of many climate-friendly initiatives, the aviation sector must become more sustainable. A potential path for regional airliners could be the installation of hybrid-electric powertrains. In this work, a conceptual study design of various powertrain architectures is conducted. This helps the designer to quickly generate approximate numbers on the basic characteristics of new aircraft configurations. These results can be used to advance subsystems modeling or improve the starting values in the following preliminary aircraft design. After the selection of representative architectures, reasonable technological assumptions were gathered, ranging between a conservative and an optimistic scenario. This was done for powertrain components, various energy storage concepts and structural and aerodynamic changes. The initial sizing method was developed by building two interconnected sizing iteration loops. In addition, a safety assessment was integrated due to the many unconventional components in the powertrain’s setup. The results show that the fuel consumption of a conventional aircraft is not undercut with a hybrid-electric powertrain aircraft based on conservative technological assumptions. In the optimistic scenario, however, selected powertrain architectures show a significant drop in fuel consumption when compared to the conventional one. Furthermore, the use of synergistic effects and systematic powertrain optimizations can decrease the fuel consumption even further. In conclusion, it was shown that this initial sizing method can calculate entire hybrid-electric aircraft designs on a conceptual level. The results can quickly present trends that are reasonable and helpful. In addition, the safety assessment first gives evidence about which levels of safety have to be considered for the different components in the development of hybrid-electric powertrains.